2020
DOI: 10.3389/fneur.2020.584734
|View full text |Cite
|
Sign up to set email alerts
|

Reductions in Hospital Admissions and Delays in Acute Stroke Care During the Pandemic of COVID-19

Abstract: Background: Rapid and effective medical care for stroke is paramount to achieve maximal functional recovery. Because of the wide spreading of the coronavirus disease in 2019 (COVID-19), acute stroke care is negatively impacted. How much acute care for stroke has been affected during the pandemic remains to be assessed. Methods: The first-level response to major public health was launched from January 24th to April 29th, 2020 in Beijing to contain the spread of COVID-19. Based on a database connecting all 77 st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
54
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 41 publications
(59 citation statements)
references
References 36 publications
4
54
0
Order By: Relevance
“…This is in accordance with published reports from across the world [ 1 – 3 , 6 8 , 11 13 ]. A decrease in stroke activation codes and stroke admissions has been reported, and since the reduction has been mainly described for mild or moderate strokes, patient-related factors and avoidance behaviour due to COVID-19 have been postulated [ 1 – 3 , 6 8 , 11 13 ]. This behaviour may have the unfortunate consequence that people with strokes not seeking help during the pandemic may be at increased risk of future recurrent strokes due to the lack of optimal secondary prevention [ 16 ].…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…This is in accordance with published reports from across the world [ 1 – 3 , 6 8 , 11 13 ]. A decrease in stroke activation codes and stroke admissions has been reported, and since the reduction has been mainly described for mild or moderate strokes, patient-related factors and avoidance behaviour due to COVID-19 have been postulated [ 1 – 3 , 6 8 , 11 13 ]. This behaviour may have the unfortunate consequence that people with strokes not seeking help during the pandemic may be at increased risk of future recurrent strokes due to the lack of optimal secondary prevention [ 16 ].…”
Section: Discussionsupporting
confidence: 93%
“…Many stroke centres have reported that COVID-19 discourages patients from contacting the health care system with an increase in prehospital delay and decrease in stroke admissions as a result [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. We have previously reported a decrease of almost 1/3 in stroke admissions in relation to the lockdown in Norway [6].…”
Section: Introductionmentioning
confidence: 71%
See 3 more Smart Citations